The Effect of Coloring Stimulation to Improve Children's Fine Motor Development at Aisyiyah Kindergarten Sungai Alang Branch Karang Intan - Melati Jayusman; Evi Risa Mariana; Evy Marlinda; Agus Rachmadi; Rizkan Azhima (Poltekkes Kemenkes Palu, 2025)
Preschool children (ages 3–6 years) are in their golden age of development, during which physical and psychological maturity progress rapidly. Fine motor skills are particularly important, as they support later academic abilities such as writing and drawing. This study aimed to determine the effect of coloring stimulation on the fine motor development of preschool children at Aisyiyah Kindergarten, Sungai Alang Branch, Karang Intan. This research employed a quantitative, quasi-experimental design using one group pretest–posttest without a control group. The study involved 18 children in class B. Fine motor development was measured using an observation rubric, and data were analyzed with the Wilcoxon signed-rank test. Before the intervention, the mean fine motor score was 3.89 (range 3–5). After five sessions of coloring stimulation, the mean score increased to 10.11 (range 8–12). Statistical analysis showed a significant difference (p-value=0.001, p<0.005), indicating that coloring stimulation had a measurable impact on children’s fine motor development. Coloring stimulation significantly improves preschool children’s fine motor skills. Both teachers and parents are encouraged to provide regular coloring activities as a simple, enjoyable, and effective strategy to optimize children’s developmental outcomes.